Implementasi Fungsi Organisasi Melalui Kegiatan Pemetaan Kawasan Rawan Dan Rentan Narkoba Di Kota Bengkulu - Marlianto, Nuche; RS, Danur Azissah; Pebriani, Emi; Ramlis, Ravika; Hermiati, Dilfera (Jurnal Dehasen Untuk Negeri, 2024)
Narcotics and psychotropic substances are drugs, materials that are useful in the field of health care, but on the other hand can cause dependence which is very detrimental if used without strict supervision. Narcotic substances were originally indicated for medicinal purposes, but with the development of science and technology, types of narcotics can be misused. Drug abuse has become a serious problem in various countries, both in developed countries and in Indonesia. To deal with the problem of narcotics, the activity "Implementation of Organizational Functions Through Mapping Activities of Drug Prone and Vulnerable Areas in Urban Children and Youth in 2024 at the Kandang Village Office, Kampung Melayu District, Bengkulu City" was carried out. The purpose of this activity is to realize a clean city from drugs. In the community service activities that have been carried out, it is considered very important. The results achieved in the formation of Volunteers, Intelligence in the Working Area of Kelurahan Kandang, Kampung Melayu Subdistrict, Bengkulu City, whose members consist of local people, both youth and youth organizations as well as community leaders who are chosen and trusted by the community. They will help socialize and control community activities, including monitoring and controlling those suspected of being involved in consuming or distributing drugs. Assistance to the cadres has been provided in health services and counseling activities, not only related to drugs but also other health issues, through technical guidance from BNN Bengkulu City.